Atomic Level Insights into Metal Halide Perovskite Materials by Scanning Tunneling Microscopy and Spectroscopy. Issue 5 (8th November 2021) - Zhang, Wei; Ono, Luis K.; Xue, Jiamin; Qi, Yabing
Abstract: Metal halide perovskite materials (MHPMs) have attracted significant attention because of their superior optoelectronic properties and versatile applications. The power conversion efficiency of MHPM solar cells (PSCs) has skyrocketed to 25.5 %. Although the performance of PSCs is already competitive, several important challenges still need to be solved to realize commercial applications. A thorough understanding of surface atomic structures and structure–property relationships is at the heart of these remaining issues. Scanning tunneling microscopy (STM) and spectroscopy (STS) can be used to characterize the surface properties of MHPMs, which can offer crucial insights into MHPMs at the atomic scale. This Review summarizes recent progress in STM and STS studies on MHPMs, with a focus on the surface properties. We provide understanding from the comparative perspective of several different MHPMs. We also highlight a series of novel phenomena observed by STM and STS. Finally, we outline a few research topics of primary importance for future studies. Abstract : Scanning tunneling microscopy and spectroscopy are powerful techniques to visualize the topographic and electronic structures of metal halide perovskites with atomic‐level resolution. These techniques can also be used to reveal the dynamics of surface defects and charge carriers as well as on‐surface reactions and optoelectronic properties at the surface and interfaces of perovskite materials.